Reading aloud activities as a way to determine students’ narrative template (2004)
This article focuses on the description of a methodological innovation implemented in a beginner’s English class at university level in Bogotá, Colombia which had two aims: First, to explore the role of reading aloud activities in the teaching of English, and second, to describe the narrative template students use when retelling a story in writing. Data collection sources for this smallscale project incorporated class observation during the reading aloud activity, students’ written samples as the means for them to retell the story, and interviews that were held at the end of the research process. This experience allowed both the teacher and the learners to approach English and see themselves playing a different role in the classroom. Moreover, it helped students foster their communicative competence as well as their motivation toward English language learning. Thus, this study promotes pedagogical debate about literacy processes in English in adults and the applicability of this kind of innovation in an EFL context. Key words: Literacy, Reading Aloud, Storytelling, Narrative Template, English Innovation, Foreign Language-Innovation El objetivo de este artículo es describir una innovación que se implementó en un curso de inglés básico a nivel universitario en Bogotá, Colombia y el cual tuvo dos objetivos: primero, explorar el rol de de las actividades de lectura en voz alta para el aprendizaje del Inglés y segundo describir el modelo narrativo que usan los estudiantes cuando narran una historia. Los métodos de recolección de datos para este proyecto a menor escala incorporaron observación de clases durante las actividades de lectura en voz alta, producción escrita de los estudiantes como un medio para que ellos narraran las historias y entrevistas al final del proceso de investigación. Esta experiencia permitió al profesor y a los estudiantes acercase al inglés de una manera diferente y verse a sí mismos asumiendo otro rol en el aula de clase. Además, incentivó el desarrollo de la competencia comunicativa así como la motivación hacia el aprendizaje de la lengua. En consecuencia, este estudio promueve la discusión pedagógica acerca del proceso de desarrollo de lectura y escritura en inglés en adultos y la aplicación de este tipo de innovación en un contexto de enseñanza del inglés como lengua extranjera. Palabras claves: Proceso Lecto-escritor, Lectura en voz alta, Narración- Historias, Modelo Narrativo, Inglés-Innovaciones, Innovación- Lengua Extranjera